GAMBARAN PERESEPAN OBAT PADA PASIEN DIARE DI PUSKESMAS JAMBI KECIL TAHUN 2020 - Faila Sufa; Armaidi Darmawan; Nyimas Natasha Ayu Shafira; Rina Nofrienis; Erny Kusdiyah (Journal of Medical Studies, 2021)
ABSTRACT Background: Diarrhea remains a serious health problem since it is a leading cause of death. Improper treatments are the main cause of death from diarrhea. One of ways to prevent this is to use rational drugs, which can be assessed using WHO prescribing indicators. Objectives: This study aims to determine drug prescribing for diarrhea patients at the Jambi Kecil Health Center in 2020. Methods: A quantitative descriptive study with a sample of 115 prescriptions for diarrhea patients at the Jambi Kecil Health Center in 2020 (total sampling). Results: Diarrhea was highest in female (56,5%) and among 0-4 years old age group (34,8%), the most frequently prescribed antidiarrheal drugs was oral rehydration solution (15,2%), the average number of drugs prescribed was 3.37, the drugs prescribed by generic name was 94,1%, the encounters with an antibiotic prescribed was 42,6%, the encounters with an injection prescribed was 0%, the drugs prescribed from DOEN was 76,8%. Conclusions: Oral rehydration solutions were the most prescribed drugs, the percentage of drugs prescribed by generic name and injection were in accordance wtih WHO indicators, while the average number of drugs prescribed, the percentage of antibiotic, and drugs prescribed from DOEN were not in accordance with WHO indicator standards. Keywords: prescribing, diarrhea, WHO indicators ABSTRAK Latar Belakang: Diare merupakan masalah kesehatan dengan angka kematian yang tinggi. Tatalaksana yang tidak tepat dan cepat merupakan penyebab utama kematian akibat diare. Salah satu pencegahannya adalah dengan penggunaan obat rasional, yang dapat dinilai menggunakan indikator peresepan WHO. Tujuan: Mengetahui gambaran peresepan obat pasien diare di Puskesmas Jambi Kecil tahun 2020. Metode: Penelitian deskriptif kuantitatif dengan sampel 115 resep (total sampling) pasien diare di Puskesmas Jambi Kecil tahun 2020. Hasil: Distribusi pasien diare terbanyak adalah perempuan (56,5%), kelompok usia terbanyak 0-4 tahun (34,8%), obat diare terbanyak diresepkan adalah cairan rehidrasi oral (15,2%), rerata jumlah item obat per lembar resep 3,37 item, peresepan obat generik 94,1%, peresepan antibiotik 42,6%, peresepan injeksi 0%, dan peresepan dari DOEN 76,8%. Kesimpulan: Cairan rehidrasi oral merupakan obat yang paling banyak diresepkan, persentase peresepan obat generik dan injeksi sesuai indikator WHO, sedangkan rata-rata jumlah item obat per lembar resep, persentase antibiotik, dan peresepan dari DOEN tidak sesuai standar indikator WHO. Kata kunci : peresepan, diare, indikator WHO